IDENTIFIKASI Aquilaria malaccensis DAN A. microcarpa MENGGUNAKAN PENANDA RAPD - Anto Rimbawanto; AYPBC Widyatmoko (Jurnal Pemuliaan Tanaman Hutan, 2011)
Aquilaria sp, belong to Family Thymelaeaceae, is one of several species whose can produce agarwood or gaharu. Quality of gaharu of this species is better than the other species. With high economic value, demand of Aquilaria sp increase and also increase exploitation of the species without counterbalanced by enough planting activity. Therefore, conservation and breeding program of the species become important to carry out. Two important Aquilaria sp.  are A. malaccensis and A. microcarpa. However, both species only can be distinguished by generative characteristics such as flower and fruit. The most appropriate and rapid method to identify species is DNA marker, especially using RAPD markers. In order to obtain DNA marker to species identification, 2 selection steps should be carried out. The first step was using 2-3 samples per species. From 180 RAPD primers, only 5 primers produced loci those can identify both species, those are D-20, A-17, G-12, R-15 and U-13. The second selection step was carried out by increasing number of samples per species (24 samples in total). From the five primers obtained from first selection, only U-13 700 basepairs that can be selected as species-specific DNA markers to identify both Aquilaria sp.